“Effects of Oxygen Transference on Protease Production by Rhodotorula mucilaginosa CBMAI 1528 in a Stirred Tank Bioreactor “ - Machado, Suellen (2022)
“Microbial proteases, especially aspartic proteases, are an essential group of enzymes produced from different microorganisms. Microbial proteases have several applications, mainly in the food, beverage, cosmetic, and pharmaceutical industries, due to their efficiency in the processing and in the manufacturing stages. The yeast Rhodotorula mucilaginosa CBMAI 1528 was isolated from the Antarctic environment and was previously reported to have higher extracellular aspartic protease production. In addition, advances in the operational conditions of bioreactors for enzyme production are important to reduce the gap associated with scaling−up processes. This is the first study that evaluates the influence of oxygen transference (kLa) on the protease production of R. mucilaginosa yeast. To that end, batch cultures were created in a stirred tank bioreactor using Sabouraud dextrose broth at 25 ◦C for 72 h under kLa values from 18 to 135 h−1 . The results show that kLa (121 h−1 ) obtained at 500 rpm and 1.5 vvm plays an important role in protease production (124.9 U/mL) and productivity (6.784 U/L.h) as well as biomass (10.4 g/L), µmax (0.14 h−1 ) and Yx/s (0.484 g/g). In conclusion, R. mucilaginosa showed high yield production in aerobic culture with the efficiency of protease expression and secretion influenced by kLa. In this sense, our results could be used for further industrial investment.“